2019
DOI: 10.1111/myc.12917
|View full text |Cite
|
Sign up to set email alerts
|

Creation and assessment of a clinical predictive model for candidaemia in patients with candiduria

Abstract: Summary Candidaemia is the most common clinical presentation of invasive candidiasis and is a major cause of morbidity and mortality. Candiduria is a predictor for candidaemia; however, patient characteristics that are associated with concurrent candidaemia in the setting of candiduria are unclear. Identifying these characteristics could aid in the early detection of systemic disease. We performed a retrospective cohort analysis of hospitalised patients with candiduria at our institution over a 13‐year period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
2
11
0
1
Order By: Relevance
“…The Candida score by Leon et al [11] is the most common scoring tool to predict candidaemia in ICUs and has been externally validated with fair to good discrimination. However, the risk factors included in the multivariate analysis were determined first by univariate analysis, as in the works by Wang et al [29] and Cuervo et al [30]. This approach is incorrect, as a univariate model is less comprehensive and does not consider relationships between different factors, making the final model prone to serious confusion bias, inclusion of false positives and exclusion of false negatives.…”
Section: Discussionmentioning
confidence: 99%
“…The Candida score by Leon et al [11] is the most common scoring tool to predict candidaemia in ICUs and has been externally validated with fair to good discrimination. However, the risk factors included in the multivariate analysis were determined first by univariate analysis, as in the works by Wang et al [29] and Cuervo et al [30]. This approach is incorrect, as a univariate model is less comprehensive and does not consider relationships between different factors, making the final model prone to serious confusion bias, inclusion of false positives and exclusion of false negatives.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 6 Candiduria is not only a marker for seriously ill patients that need particular attentions, but also an independent risk factor for invasive candidiasis (IC). 7 For example, the Infectious Diseases Association of America (IDSA) guidelines (2016 version) emphasized the importance of treatment for candiduria patients under high-risk candidiasis conditions. A molecular correlation between Candida strains isolated from candidemia and concomitant candiduria indicated that hematogenous dissemination possibly existed in ICU candiduria patients.…”
Section: Introductionmentioning
confidence: 99%
“…К предрасполагающим факторам развития кандидемии на фоне кандидурии относят: стационарное лечение в течение 12 и более суток, наличие центрального венозного катетера, парентеральное питание, онкологическое заболевание тазовых органов и крови, лечение ингибиторами бета-лактамаз, почечную недостаточность, лихорадку, нейтропению, нейтрофилию, сахарный диабет, наличие гастростомы [42].…”
Section: факторы риска кандидоза мочевыводящих путейunclassified